Antihyperlipidemic and hepatoprotective activities of residue polysaccharide from Cordyceps militaris SU-12. (20th October 2015) - Wang, Liqin; Xu, Nuo; Zhang, Jianjun; Zhao, Huajie; Lin, Lin; Jia, Shouhua; Jia, Le
Highlights: Medium residue polysaccharide (RPS) from Cordyceps militaris SU-12 was isolated. Glycosidic bond types and Molecular weight were characterized. Three monosaccharide components of RPS were confirmed. Antihyperlipidemic and hepatoprotective activities were investigated in vivo . Antioxidant analysis of RPS in vivo was processed. Abstract: Cordyceps militaris has been artificially cultivated in China, and the great amounts of produced medium residue were discarded after the harvest. The aims of this work were to analyze the structure of the residue polysaccharide (RPS) of C. militaris SU-12, and to investigate the pharmacological effects of RPS on lipid metabolism and oxidative stress. RPS was composed of glucose, arabinose and mannose with a ratio of 62:1.6:1 by gas chromatography analysis, and the Mw (weight-average molecular weight), Mn (number-average molecular weight) and Mz ( z -average molecular weight) of RPS were 2.86 × 10 3, 6.85 × 10 2, and 1.97 × 10 4 Da, respectively. The mice experiments demonstrated that RPS could reduce the levels of blood and liver lipid, and improve the glutamate pyruvate transaminase and antioxidant activity. The histopathological observations of mice livers indicated that RPS could attenuate liver cell injury. Results suggest that the RPS might be used as a potential antihyperlipidemic, hepatoprotective and antioxidant product.